Study on Horizontally Polarized Omnidirectional Microstrip Antenna - Kun Wei; Jian-ying Li; Ling Wang; Zi-jian Xing; Rui Xu (International Journal of Antennas and Propagation)
A horizontally polarized omnidirectional microstrip antenna is proposed in this paper. The structure of designed antenna is with two back-to-back horizontally polarized microstrip antenna elements. Gain variation on main radiation plane of this new antenna is analyzed and radiation theory is deduced; formula of directivity on main radiation plane is given. Better omnidirectional characteristic of this antenna can be obtained by decreasing patch physical length. Both simulated and measured results verify the omnidirectional radiation patterns and input impedance characteristics. Good omnidirectional radiation patterns (gain variation in E-plane less than ±0.4 dBi) and input impedance characteristics are obtained; moreover, cross polarization less than −20 dBi is achieved.